Magnetic forces enable controlled drug delivery by disrupting endothelial cell-cell junctions - Yongzhi Qiu (Nature Portfolio, 2017)
The transportation of large molecules through the vascular endothelium presents a major challenge forin vivodrug delivery. Here, the authors demonstrate the potential of using external magnetic fields and magnetic nanoparticles to enhance the local extravasation of circulating large molecules.